Meeting China halfway : how to defuse the emerging US-China rivalry - Goldstein, Lyle (Georgetown University Press, 2015)
China's expanding economic and military power, and the US response to the challenge of China's rise are shaping international relations in the twenty-first century. A breakdown in this relationship could bring about a situation reminiscent of the Cold War. Lyle Goldstein argues that while conflict is not predetermined, there are worrying signs that the relationship is becoming an increasingly chilly and dangerous rivalry. The main purposes of this book are to analyze the trajectory of the relationship, to examine both US views and Chinese views of the other, and to propose concrete steps to reverse a perilous deterioration in the relationship. He examines key flash points or difficult issues in the US-China relationship in depth, such as Taiwan, the Korean Peninsula, Japan, economic issues, and climate change, to name a few. A unique feature of the book is that Goldstein's language skills allowed him to incorporate Chinese military and diplomatic publications to a degree that few in the West have been able to in the past. Goldstein is under no illusions that compromise is easy, but he calls for both the US and China to take steps to seek an accommodation of interests in the Pacific and globally to avoid a dangerous strategic rivalry.